Karakteristik Getaran Mesin Penggerak Berbahan Bakar Biogas dengan Analisis Fast Fourier Transform (FFT) - Rusmiyatun, Rusmiyatun; Al manan, Oesman Raliby; Andriyanto, Andriyanto; Kurniawan, Sofyan; Munahar, Suroto (Universitas Muhammadiyah Magelang, 2025)
Sambak Village is a tofu industry Micro, Small, and Medium Enterprises (MSMEs) area that produces biogas under the auspices of the Sambak Sustainable Biogas Group (KBLS). This MSME is located in Kajoran District, Magelang Regency, Central Java. The Sambak Tofu Industry MSME faces several problems, including the relatively high production costs for tofu production. This condition is caused by the soybean milling process, which is the initial process of tofu production, still using a drive engine with fossil fuels/diesel which has a fairly high price, thus having an impact on reducing the profits of the Sambak tofu industry MSME. Therefore, efforts are needed to optimize the use of biogas as a driving engine energy for soybean milling, and manage the distribution of biogas used by every household user and tofu industry MSME. Seeing these problems, this activity will design a driving engine with biogas fuel equipped with a synchronizer system and equipped with vibration analysis produced.